A regulamentação do exercício profissional da arquitetura no Brasil. - Oliveira, Antonio Francisco de (2012)
This thesis examines in depth the system set up by the central government in 1933 to control the professional practice of building designers in Brazil the Confea-Crea as well as historical factors that led do its creation, such as the progressive emergence of similar systems in other countries and the evolution of that practice and of the modes of training the designers in question. The Confea-Crea was given competence to supervise equally the professional practice of engineers who were not building designers, as mechanical and electrical engineers, and this gradually made the architects dissatisfied, which brought about their desire to leave the multi-professional Confea-Crea and to create their own regulatory system congregating exclusively architects. The thesis focus on the period of time starting in 1933 and ending in 2007 (the year of the last unsuccessful attempt of the architects to create their own system of professional control), but the historical analysis it presents begins with facts belonging to the Renaissance era.